Pengaruh Literasi Keuangan Terhadap Kesejahteraan Finansial Dengan Pengelolaan Keuangan Sebagai Variabel Intervening: Pada Ibu Rumah Tangga Di Dusun Wonosari Timur - Marwa Marwa; Sultan Sultan; Sahrir Sahrir (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the effect of financial literacy on financial well-being with financial management as an intervening variable. The method used in this study is quantitative. The population of this study consisted of housewives in Kamanre Village, Wonosari Timur Hamlet. The research sample was determined using the Slovin formula, so that 98 housewife respondents were obtained. Data collection was carried out through questionnaires, while data analysis included validity tests, reliability tests, regression analysis, and path analysis using SPSS 25. After that, the Sobel test was carried out using the Sobel calculator online. Based on the results of the analysis, financial literacy was proven to have an effect on financial well-being. Financial literacy also has an influence on financial management, which then acts as a mediating variable in the relationship between financial literacy and financial well-being. These findings underline the importance of increasing financial literacy among housewives, in order to encourage more optimal family financial management. Through adequate understanding of financial planning and saving habits, housewives have the potential to manage financial resources more efficiently to support family welfare.